Fermi level depinning by a C-containing layer in a metal/Ge structure by using a chemical bath - 王巍 王敬 赵梅 梁仁荣 许军 (Journal of semiconductors, 2012)
Insertion of a C-containing layer in a metal/Ge structure,using a chemical bath,enabled the Schottky barrier height（SBH） to be modulated.Chemical baths with 1-octadecene,1-hexadecene,1-tetradecene,and 1- dodecene were used separately with Ge substrates.An ultrathin C-containing layer stops the penetration of free electron wave functions from the metal to the Ge.Metal-induced gap states are alleviated and the pinned Fermi level is released.The SBH is lowered to 0.17 eV.This new formation method is much less complex than traditional ones,and the result is very good.